THEME AND IDEA FEATURES OF VLADIMIR NABOKOV’S “THE REAL LIFE OF SEBASTIAN KNIGHT” NOVEL - Azizaliyeva, Basira (Revista Inclusiones, 2020)
Vladimir Nabokov’s “The Real Life of Sebastian Knight” novel, points to the creative personality and society, the loneliness of man, the metaphysical meaning of artistic expression, real and true life, death, unity of spirit. The consistently developing plot logic is aligned and the unity of the spirit is the main idea of the novel, and the moment that the deprivation of physical life can not be an obstacle to the unity of the spirit develops against the background of a specific and original trio: the author of the novel, the novelist and the hero of the novel. The analysis of the work is based on methods of comparative studies using methods of literary and psychological analysis, the theoretical features of postmodernism, Freudianism. Autobiographical characteristics of the novel created conditions for parallels between the events of the novel and the historical and comparative method of life and creativity of the writer.